A microfluidic ExoSearch chip for multiplexed exosome detection towards blood-based ovarian cancer diagnosis - Zhao, Z.; Yang, Y.; Zeng, Y.; He, Mei (My University, 2015)
Tumor-derived circulating exosomes, enriched with a group of tumor antigens, have been recognized as a promising biomarker source for cancer diagnosis via a less invasive procedure. Quantitatively pinpointing exosome tumor markers is appealing, yet challenging. In this study, we developed a simple microfluidic approach (ExoSearch) which provides enriched preparation of blood plasma exosomes for in situ, multiplexed detection using immunomagnetic beads. The ExoSearch chip offers a robust, continuous-flow design for quantitative isolation and release of blood plasma exosomes in a wide range of preparation volumes (10 mu L to 10 mL). We employed the ExoSearch chip for blood-based diagnosis of ovarian cancer by multiplexed measurement of three exosomal tumor markers (CA-125, EpCAM, CD24) using a training set of ovarian cancer patient plasma, which showed significant diagnostic power (a. u. c. = 1.0, p = 0.001) and was comparable with the standard Bradford assay. This work provides an essentially needed platform for utilization of exosomes in clinical cancer diagnosis, as well as fundamental exosome research.
Citation: Zhao, Z., Yang, Y., Zeng, Y., & He, M. (2016). A microfluidic ExoSearch chip for multiplexed exosome detection towards blood-based ovarian cancer diagnosis. Lab on a Chip, 16(3), 489-496. doi:10.1039/c5lc01117e
Keywords: Nanoparticle Tracking Analysis; Tumor-Derived Exosomes; Extracellular; Vesicles; Circulating Exosomes; Electron-Microscopy